Neural signature of tDCS, tPCS and their combination: Comparing the effects on neural plasticity. (10th January 2017) - Thibaut, Aurore; Russo, Cristina; Morales-Quezada, Leon; Hurtado-Puerto, Aura; Deitos, Alícia; Freedman, Steven; Carvalho, Sandra; Fregni, Felipe
Highlights: Does the combination of different NIBS techniques influence brain activity? tPCS increases power in alpha bandwidth by influencing bottom-up connectivity. tDCS has an impact on beta activity through top-down pathways. Combining tDCS and tPCS, applied simultaneously, decreases cortical excitability. Abstract: Transcranial pulsed current stimulation (tPCS) and transcranial direct current stimulation (tDCS) are two noninvasive neuromodulatory brain stimulation techniques whose effects on human brain and behavior have been studied individually. In the present study we aimed to quantify the effects of tDCS and tPCS, individually and in combination, on cortical activity, sensitivity and pain-related assessments in healthy individuals in order to understand their neurophysiological mechanisms and potential applications in clinical populations. A total of 48 healthy individuals participated in this randomized double blind sham controlled study. Participants were randomized to receive a single stimulation session of either: active or sham tPCS and active or sham tDCS. Quantitative electroencephalography (qEEG), sensitivity and pain assessments were used before and after each stimulation session. We observed that tPCS had a higher effect on power, as compared to tDCS, in several bandwidths on various cortical regions: the theta band in the parietal region (p = 0.021), the alpha band in the temporal (p = 0.009), parietal (p = 0.0063), and occipital (p < 0.0001) regions. We found that the combination of tPCS and tDCS significantly decreased power in the low beta bandwidth of the frontal (p = 0.0006), central (p = 0.0001), and occipital (p = 0.0003) regions, when compared to sham stimulation. Additionally, tDCS significantly increased power in high beta over the temporal (p = 0.0015) and parietal (p = 0.0007) regions, as compared to sham. We found no effect on sensitivity or pain-related assessments. We concluded that tPCS and tDCS have different neurophysiological mechanisms, elicit distinct signatures, and that the combination of the two leads to no effect or a decrease on qEEG power. Further studies are required to examine the effects of these techniques on clinical populations in which EEG signatures have been found altered.